НЕТИПОВІ (ГІБРИДНІ) ФОРМИ ДЕРЖАВНО-ТЕРИТОРІАЛЬНОГО УСТРОЮ У КОНСТИТУЦІЙНОМУ ПРАВІ ВЕЛИКОЇ БРИТАНІЇ - Сокирська, Наталія Анатоліївна (SUPREMANCE OF LAW, 2019)
In this article author comprehensively analyzed legal regulations characteristics and patterns of the establishment and development of the atypical (hybrid) forms of state-territorial structure, varieties of their forms and types in the institutional system of the Commonwealth of Nations. The Commonwealth of nations arose from the British Empire as the structure that regulates relationships between former metropolis and former dependent territories. The Commonwealth has come a long way of transformation. Academic literature and sources of the research were analyzed. It was defined the essence and meaning of the atypical (hybrid) forms of state-territorial structure as well as indicated the reasons for appearance of the atypical (hybrid) forms of state-territorial structure of the British Empire. It was also defi ned and characterized main phases of the British colonial administrations transformation. Atypical relations between members of the Commonwealth of Nations determine the singularity of organizational structure and informality of relations between these members. Evolutionary path of the British Empire’s transformation as well as establishment of independence of countries which were its members and new forms of their relationships with metropolis needs further researches considering trends of the formation of state territory in the modern world. Atypical (hybrid) forms of territorial structure that appeared during the process of the transformation of the British Empire into the British Commonwealth of nations at first, and then - into the Commonwealth of nations convince to analyze the topic deeper. Provisions of normative documents were reviewed and the process of legal regulation of the atypical (hybrid) forms of state-territorial structure was outlined.
Keywords: state-territorial structure; atypical (hybrid) forms; the British Empire; the Commonwealth of nations; dominion